The Islamic Education in Guinea: Traditional Development and Muhammadiyah’s Modern Reforms: A Comparative Study - Balde, Thierno Abdoulaye; Arifin, Syamsul (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2026)
This study examines the development of Islamic education in Guinea and Muhammadiyah’s modern education reforms through a qualitative comparative approach of secondary data. Drawing on existing literature, the paper analyses the historical trajectories, institutional frameworks, curriculum orientation, pedagogical applications, and reform orientations in both contexts. The findings reveal that Islamic education in Guinea remains predominantly community-based, decentralised, and centred on Qur’anic memorisation, thereby ensuring religious continuity but limiting institutional integration, curriculum diversification, and broader socio-economic mobility for learners. In contrast, Muhammadiyah represents a reform-oriented educational model characterised by centralised governance, curriculum integration combining religious and general sciences, and pedagogical innovation. Its system also reflects a strong commitment to social transformation and community development. The study argues that the modernisation of Islamic education does not necessarily imply secularisation but rather depends on institutional capacity, contextual adaptation, and policy support. The paper contributes to comparative Islamic education scholarship by offering context-sensitive insights for reform in under-researched settings such as West Africa.